2019
DOI: 10.1039/c9ra03287h
|View full text |Cite
|
Sign up to set email alerts
|

A new iron-based metal–organic framework with enhancing catalysis activity for benzene hydroxylation

Abstract: A new Fe-based MOFs catalyst was used for benzene hydroxylation with the high phenol yield (64.5%) and selectivity (92.9%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…8 Tu has synthesized a novel Fe-based MOF with a topological framework as a recyclable heterogeneous catalyst for benzene hydroxylation. 9 The Yang group reported a mixed valent Fe-based MOF, which greatly enhanced Fenton performance and further improved the efficiency of benzene hydroxylation to produce phenol. 10 To a certain extent, although MOF materials could be applied to the direct hydroxylation of benzene to prepare phenol, its limited response to light impeded its wide application.…”
Section: Introductionmentioning
confidence: 99%
“…8 Tu has synthesized a novel Fe-based MOF with a topological framework as a recyclable heterogeneous catalyst for benzene hydroxylation. 9 The Yang group reported a mixed valent Fe-based MOF, which greatly enhanced Fenton performance and further improved the efficiency of benzene hydroxylation to produce phenol. 10 To a certain extent, although MOF materials could be applied to the direct hydroxylation of benzene to prepare phenol, its limited response to light impeded its wide application.…”
Section: Introductionmentioning
confidence: 99%
“…The crystallographic micropore sizes of JXNU-5 and NU-1000 range between 5 and 9 Å [24,42] and may be suitable for SF 6 sorption. We previously demonstrated that pore sizes of ~7 Å could enhance the sorption of SF 6 (5.5 Å kinetic diameter [36]) on mixed-linker ZIF-7-8s [43].…”
Section: Pure Gas Sorption On Tbapy-mofsmentioning
confidence: 99%
“…[ 59–62 ] Due to their unique characteristics, they were usually used as catalysts in light and electric fields. [ 63–67 ] Except for that, acting as electrode materials for SCs, several groups utilized the Cr‐based MIL compositing with conductive units to prepare the electrodes in recent years. [ 68,69 ] As to Fe‐based MOFs, to date, they have only scarcely been investigated for SCs probably due to the more insufficient conductivity and lower degree of crystallinity.…”
Section: Fe‐based Mofsmentioning
confidence: 99%